2018
DOI: 10.1021/acs.analchem.7b04544
|View full text |Cite
|
Sign up to set email alerts
|

Self-Catalyzing Chemiluminescence of Luminol-Diazonium Ion and Its Application for Catalyst-Free Hydrogen Peroxide Detection and Rat Arthritis Imaging

Abstract: We report the unique self-catalyzing chemiluminescence (CL) of luminol-diazonium ion (N-luminol) and its analytical potential. Visual CL emission was initially observed when N-luminol was subjected to alkaline aqueous HO without the aid of any catalysts. Further experimental investigations found peroxidase-like activity of N-luminol on the cleavage of HO into OH radical. Together with other experimental evidence, the CL mechanism is suggested as the activation of N-luminol and its dediazotization product 3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 60 publications
(68 reference statements)
0
29
0
2
Order By: Relevance
“…[19] In the kinetic study by using UV/Vis spectroscopy,a nd ecreasing catalytic rate was observed after adding SOD (Figure 3b), which indicated the coexistence of CO 2 À . [20] Thep otential COH À was also monitored by ESR as well, followed by the same experiment condition using 5,5-dimethyl-1-pyrroline N-oxide (DMPO) as as pin trapping agent to form DMPO-OH adduct. However,t he distinct 4-fold characteristic peaks were not clearly observed, depicting COH À was not the major ROSi ntermediates (Supporting Information, Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…[19] In the kinetic study by using UV/Vis spectroscopy,a nd ecreasing catalytic rate was observed after adding SOD (Figure 3b), which indicated the coexistence of CO 2 À . [20] Thep otential COH À was also monitored by ESR as well, followed by the same experiment condition using 5,5-dimethyl-1-pyrroline N-oxide (DMPO) as as pin trapping agent to form DMPO-OH adduct. However,t he distinct 4-fold characteristic peaks were not clearly observed, depicting COH À was not the major ROSi ntermediates (Supporting Information, Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Thediscussion in the previous section on light-responsive materials revealed the importance of light as trigger for selfreporting properties.However,light is not only able to induce the self-reporting,b ut may also be the self-reporting characteristic itself.L ight as direct output of ac hemical reaction, that is,c hemiluminescence (CL), [122][123][124][125] offers beneficial advantages such as high sensitivity and real-time monitoring over awide dynamic range without the need for sophisticated equipment. [124,[126][127][128][129][130] Therefore,CLreactions find widespread applications in biomedical or analytical fields with ongoing research for persistent improvement. However,the challenge to gain higher CL quantum yields,tune the emission range,or simplify the CL system is to modify the reaction environment or the luminophore itself in such away that the CL properties are not diminished accidentally.Nevertheless,recent research into common luminophores,s uch as dioxetanes, [131,132] peroxyoxalates (POs), [122,[133][134][135][136][137] acridinium esters, [138][139][140][141] luminol, [129,142] and their respective derivatives,led to the development of aplethora of advanced, promising self-reporting CL systems.T he CL of acridinium esters,f or example,c an be triggered by antioxidants,e nzymes or peroxides and thus finds application in (biomedical) analytics as self-reporting sensor for these substances.…”
Section: Chemically Responsive Materialsmentioning
confidence: 99%
“…Licht als direktes Produkt einer chemischen Reaktion, die so genannte Chemilumineszenz (CL), [122][123][124][125] bietet nützliche Vorteile wie hohe Empfindlichkeit und Echtzeit-Überwachung über einen großen dynamischen Bereich ohne die Notwendigkeit von hochentwickelten Geräten. [124,[126][127][128][129][130] Daher finden CL-Reaktionen weit verbreitete Anwendungen in biomedizinischen oder analytischen Bereichen mit laufender Forschung fürs t ändige Verbesserungen. Die Herausforderung,h çhere CL-Quantenausbeuten zu erzielen, den Emissionsbereich einzustellen oder das CL-System zu vereinfachen, besteht jedoch darin, die Reaktionsumgebung oder den Luminophor selbst so zu modifizieren, dass die CL-Eigenschaften nicht versehentlich vermindert werden.…”
Section: Chemikalienresponsive Materialienunclassified